Correlation Between Direct Contact Status with Diphteria in Blitar - Ana Nur Filiya; Novy Ardyanti Putri (Universitas STRADA Indonesia, 2019)
Diphtheria is a contagion deadly disease which case increases year-by-year. Objective: To know the correlation of direct contact with diphteria patient towards diphteria in Blitar in 2016. This research method uses Observational-analytic study by using case control design. Sample in case group were 31 people of diphteria patients and 31 people of control group which is not a diphteria patients. Direct contact as Independent variable. Data were analyzed by Mc Nemar. The results showed p value is 0.21. Direct contact haven’t associated with diphteria. Further research can use more detailed questionnaire to know direct contact status properly